Plan de negocio para la creación de una nueva línea de comercialización por internet de artículos hechos en cuero en la ciudad de Manizales, Caldas (2014)
It has been necessary to develop a business plan for the Taller del Cuero Shop in the city of Manizales, in order to create a commercialization line for their products on the web, which allows reaching all market segments. By performing a detailed analysis of the company present needs, it appears that it has developed its market in a regional area, which has not sought openness to new national and international markets during the 15 years it has been in the leather goods industry. Thus this has shown that is necessary to explore new segments to show that these products made 100% of leather and with the required quality standards can penetrate the market successfully. That is why it is proposed a new commercialization line via internet for four of their star products (handbags, wallets, belts and jackets), which have been clearly identified as the most sold products in the Caldas' market. Each of the studies for the launch of the online store was developed, allowing reaching concrete and satisfactory results which conclude with the project's feasibility. Finally, the financial study is performed in order to project the necessary resources for project's implementation and operation to determine the profitability this new business generates, which is why a 5 years financial projection was done to adapt the business idea to reality. In this, it was found that for this business plan the net present value of the project is positive, indicating that it is a lossless project, it creates value for the company, its cash flows offsets the capital cost with a 20.93% surplus. The internal rate of return balances income with expenditures and makes them equivalent, ending in a profitability outlook.